Ramalan kekuatan tegangan pecah konkrit prestasi tinggi - Muhammad Fauzi Mohd. Zain,; Ade Ilham,; Hilmi Mahmud,; Wan Hamidon Wan Badaruzzaman,; Faizal Mahmud,; Kamarudin Mohd Yusof, (2003)
Splitting tensile strength is one of the concrete mechanical properties that is used in structural design. It can be related to numerous parameters which include compressive strength, water-binder ratio and concrete age. Until now, most researchers estimated the splitting tensile strength (STS) directly from compressive strength data. This paper suggests formulae that relate splitting tensile strength with that of compressive strength, water-binder ratio and concrete age. The predicted STS can be obtained accurately using these formulae. It is proposed that the equation with the concrete age (t) parameter be used in predicting the splitting tensile strength of high performance concrete